Validitas Modul Bola Tangan Bagi Mahasiswa Pendidikan Jasmani Kesehatan dan Rekreasi STKIP PGRI Lubuklinggau - Popalri Popalri; Azizil Fikri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2019)
This study aims to develop a handball module for valid Physical Health and Recreation Education STKIP PGRI Lubuklinggau students. This study uses a research and development research and development (R&D) approach, in which this research develops teaching material products in the form of handball game modules, for this research is only limited to the development stage at the validation stage. Validity test in this stage is a theoretical validity that is validation carried out by experts in their field consisting of three validators. Validation includes language validation, material / content validation and media / design validation. The results of the developed handball module meet the validity criteria with a language validity value of 94%, media / design validity of 90% and a content / material validity value of 94% which can be interpreted to be very valid. In conclusion, the handball module is very valid to be used in the learning process of students. Keywords: Module, Handball